2012
DOI: 10.1111/jpm.12022
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment and management approaches on mental health units

Abstract: This exploratory and descriptive study took place in one Canadian province. The study aimed to: (1) to identify and describe the nature and extent of current risk assessment and management approaches used in the adult inpatient mental health and forensic units; and (2) to identify good practice and shortfalls in the nature and extent of the approaches currently utilized. Data were collected from 48 participants through nine focus groups. Participants reported that they used a clinical approach to risk assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 15 publications
0
59
0
Order By: Relevance
“…In terms of assessment practices, studies describe nurses' reliance on informal unstructured processes, intuition, and 'gut feelings' to guide their assessment. In addition, ineffective safety-planning practices were also found, with studies highlighting the dissociation between riskassessment and safety-management plans (Gilbert et al 2011;Langan & Lindow 2004;Woods 2013). While some of the community mental health nurses (n = 20) in Godin's study reported using tools, they still favoured clinical judgment and 'interpretative' approaches, and relied heavily on their own 'instinct' to guide assessment.…”
Section: Risk and Mental Health Nursingmentioning
confidence: 99%
See 3 more Smart Citations
“…In terms of assessment practices, studies describe nurses' reliance on informal unstructured processes, intuition, and 'gut feelings' to guide their assessment. In addition, ineffective safety-planning practices were also found, with studies highlighting the dissociation between riskassessment and safety-management plans (Gilbert et al 2011;Langan & Lindow 2004;Woods 2013). While some of the community mental health nurses (n = 20) in Godin's study reported using tools, they still favoured clinical judgment and 'interpretative' approaches, and relied heavily on their own 'instinct' to guide assessment.…”
Section: Risk and Mental Health Nursingmentioning
confidence: 99%
“…One study was located that reported nurses using validated tools or derivatives to guide their practice (Godin 2004). In particular, little evidence of proactive safety planning and therapeutic risk taking was located, with a focus instead on crisis intervention (Delaney et al 2001;Muir-Cochrane et al 2011;Murphy 2004;Raven & Rix 1999;Trenoweth 2003;Woods 2013). In addition, ineffective safety-planning practices were also found, with studies highlighting the dissociation between riskassessment and safety-management plans (Gilbert et al 2011;Langan & Lindow 2004;Woods 2013).…”
Section: Risk and Mental Health Nursingmentioning
confidence: 99%
See 2 more Smart Citations
“…Risk assessment and safety planning is integral to the role of the mental health nurse and screening for the identification of IPV is part of this assessment (Higgins et al . ,b, Woods ). Numerous UK and Irish documents and reports provide guidelines on how to identify and manage risk in the mental health setting [The National Confidential Inquiry into Suicide and Homicide by People with Mental Illness, , National Institute for Health and Care Excellence (NICE) , Department of Health 2007; Health Service Executive ].…”
Section: Introductionmentioning
confidence: 99%